Information Management in a Dynamic Business Environment – A Case Study of Fractal Organisations - Brzozowska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
In today’s organisations, faced with constant changes in the economic environment, information management plays an important role. Greater possibilities for obtaining financial and material resources have made the implementation of economic processes less of a challenge than it used to be. Currently, the key issue is the ability to quickly acquire, effectively collect, properly process and rationally use economic information, which can bring a competitive advantage. Modern enterprises, operating in a rapidly changing environment, can use fractal theory to understand their behaviour. The concept of a fractal organisation that perfectly meets the requirements of operating in a turbulent and competitive environment can also be useful in building effective information management systems within the organisation capable of coping with the increasing volatility of the business environment. The aim of the article is to explore and explain how fractal theory and the concept of fractal organisation can help modern organisations manage information in a dynamically changing economic environment. The subject of the article is the analysis of the role of information management in the current conditions of constant changes in the economic environment in view of the ways in which organisations can use fractal theory to effectively manage information and build a competitive advantage. This article suggests descriptive and comparative analytical methods and synthetic methods of exploring and comparing different approaches to information management. In the study, statistics of measured variables as well as the Shapiro–Wilk test and Pearson’s r correlations were used to develop a multiple regression model for the dependent variable: Quality of information management.